The Linguistic Vocabulary and its Role in Constructing the Design Thought: هدى محمود عمر --- سداد هشام حميد (Al-Academy, 2019)
The importance of the Arabic language and its deep vocabulary in the live translation of the work of science and interior design can't be hidden from the whole world. The previous studies have dealt with the role of the linguistic vocabulary and Arabic calligraphy in interior spaces in terms of decoration and design. However, this research sheds light on the importance of linguistic vocabulary in the construction of design thought and how it has become the a basic motivation in the process of scientific and practical construction and not just aesthetic formations that took their place in the interior spaces, as linguistic vocabulary emerged recently and echoed within the specialization of interior design and formed a key motive to explore the roles of this vocabulary and its role in building design thought. The theoretical framework dealt with the linguistic vocabulary that has recently emerged in the field of interior design and how it has had distinctive meanings within its practical framework in the work of specialization such as (the other, the biology, the style) as models of vocabulary in scientific studies that proved the presence of a linkage between the language and interior design in providing a new scientific addition for a linguistic vocabulary and a philosophical term to reach its role in interior design as a specialized science that has gained its importance through its direct relationship to human life. The research adopted the descriptive analytical approach within the context of the second chapter. After the introduction of meanings and workings of the vocabulary, the search resulted in a set of results, the most prominent of which is that: the linguistic vocabulary gets outside its scope in the world of morale to the material world when it transforms into a language of design construction